Isocitrate Lyase in Green Leaves - Godavari, H. R. (1973)
Isocitrate lyase (EC 4.1.3.1) has been demonstrated in crude dialyzed extracts of healthy spinach (Spinacia oleracea) leaves from commercial sources and wheat (Triticum aestivum) and maize (Zea mays) leaves stored in darkness in the cold room for 1 week. The products of the reaction were identified as glyoxylate and succinate, the former by its phenylhydrazone, and the latter traced by isotopic labeling and cochromatography. Fresh spinach extracts contain a mixture of at least two endogenous inhibitors of isocitrate lyase activity and one of them is proteinaceous. The endogenous inhibitor(s) is thermostable and retains 50% of its inhibitory effect even after boiling for 10 minutes. Dark starvation of the leaves removes the inhibition, due possibly to autolysis of the inhibitor(s). The inhibitor(s) can also be removed by filtration through Sephadex gels. The crude extract from spinach shows double pH optima in phosphate buffer at pH 7.4 and pH 8.0. The apparent Km at pH 7.4 was 0.1 mm. Oxaloacetate, dl-malate, succinate, 3-phosphoglycerate, and glycolate at 10 mm concentration inhibited, but ribulose 1,5-diphosphate activated enzymic activity.